Effects of the first month of lockdown for COVID-19 in Italy: A preliminary analysis on the eyecare system from six centers. Issue 5 (September 2021) - dell'Omo, Roberto; Filippelli, Mariaelena; Semeraro, Francesco; Avitabile, Teresio; Giansanti, Fabrizio; Parmeggiani, Francesco; Romano, Mario R; Strianese, Diego; Romano, Vito; Virgili, Gianni; Costagliola, Ciro
Purpose: To compare the number of eye surgical procedures performed in Italy during the first month of lockdown with those performed in the same period in 2019. Methods: Review of the surgical procedures performed from 10 March to 9 April 2019 and from 10 March to 9 April 2020 (the first month of lockdown because of the COVID-19 outbreak) at six academic institutional centers of Italy. A distinction was made between urgent procedures: any trauma repairment, trabeculectomy/drainage implant for glaucoma, any operation for rhegmatogenous retinal detachment (RRD) repair, pars plana vitrectomy (PPV) for vitreous hemorrhage (VH), macular hole, or retained lens fragments; elective procedures: corneal transplant, phacoemulsification for cataract extraction, silicone oil removal, and PPV for epiretinal membrane; and intravitreal injections (either anti-vascular endothelial growth factor [VEGF] or dexamethasone) to treat exudative maculopathies. The main outcome measure was the rate of reduction in urgent and elective surgeries performed. Results: Overall, 3624 and 844 surgical procedures were performed from 10 March to 9 April 2019 and from 10 March to 10 April 2020, respectively (−76.7% in 2020 compared to 2019, p  < 0.0001). Urgent and elective surgical procedures and intravitreal injections of anti-VEGF drugs or dexamethasone reduced significantly in 2020 in comparison to 2019 ( p  < 0.0001 for urgent and elective surgeries and 0.01 for intravitreal injections). Conclusion: A significant reduction in the rate of urgent and elective surgeries and intravitreal injections was recorded during the first month of lockdown compared to the same period in 2019. With this analysis, the authors hope to provide some preliminary insights about the consequences of lockdown for the eyecare system in Italy.